Character Education Based on the Application of the National Education Philosophy to the Formation of Leadership among Students - Siti Aisyah, Mohamad Zin; Intan Suria, Hamzah; Muhammad Ridhwan, Sarifin; Ahmad Faizuddin, Ramli; Mohd Firdaus, Md Zain (2022)
The field of education is also undergoing a transformation in a more advanced and systematic direction. To achieve the goal of quality education, the teaching and learning process must be balanced and effective. The philosophy of education is one of the approaches to create an excellent human civilization and is able to educate students to be systematic and superior. Through philosophy, a student is able to organize his way of thinking and build a civilization using creative and critical thinking. A person's way of thinking and acting can be a motivation to do something. If thinking skills do not have a specific guide, a society will develop without a clear role and function, which contributes to waste from the point of view of the use of human capital. With Philosophy, one can find the truth, analyze, think to plan a solution and build a character that will play a role as the leader of Malaysia's transformation. The use of philosophy as a tool to purify the culture of thought in life through art and methods of thinking and human concepts. This study aims to identify the effect or impact of the implementation of the National Education Philosophy on character building among students in Malaysia. Thus, this study aims to examine the extent to which the National Education Philosophy is able to have an impact on thinking skills and building superior character. In order to achieve this goal, the method used is a literature review by examining and analyzing various articles that are relevant to the context of education in Malaysia. The data were analyzed to produce a great human character development model based on the application of the National Education Philosophy. As a result of this study, it is hoped that students will be able to see the scientific disciplines as a comprehensive idea of knowledge and linked to each other so that they are able to become students with high thinking, good character and able to solve society's problems as well as build the personality and character of excellent students.